Moog Type Syringe Pump Repair Aitecs 2016 Advance d Sryinge Pump - Muhammad Athalla Akbar; Imam Tri Harsoyo; Mohammad Rofi'i (Journal of Engineering, Electrical and Informatics, 2025)
Syringe Pump is one of the medical equipment that functions to insert medicinal liquid into patients for a certain period of time regularly. The Syringe Pump cannot function as it should. The damage that occurs to the Syringe Pump is caused by an optocoupler sensor error that causes the optocoupler sensor to not be able to push the syringe and the syringe size sensor that does not detect the size of the syringe due to ineffective use and causes the syringe size sensor to not be able to detect the size of the syringe. Therefore, improvements are needed to the sensor part of this tool so that it can detect the syringe as it functions. The repair of this Syringe Pump is carried out by measuring using a multimeter through a specified measurement point, after the results of the calculation are known, followed by the replacement of the optocoupler sensor, then gluing the broken syringe size sensor with glue, and finally testing the function of the tool with the Infusion Device Analyzer (IDA) tool so that the Syringe Pump is successfully repaired and usable. The value obtained from the measurement after making repairs to TP 1 (optocoupler sensor input) was obtained an error of 0% TP 2 (optocoupler sensor output) of 0.5%. TP 3 (syringe size sensor output) of 0%. The tool used for the function test was IDA (Infusion Device Analyzer) and obtained an average of 9.50 ml/h at the 10 ml/h setting. So it was concluded that the tool was functioning well because it was still within the tolerance limit of 10%. And the result of occlusion was 4.7 ml/h which was still at the tolerance limit.